3D‐Printed Metal–Organic Framework‐Derived Composites for Enhanced Photocatalytic Hydrogen Generation. Issue 10 (10th October 2022) - Hussain, Mian Zahid; Großmann, Paula F.; Kohler, Fabian; Kratky, Tim; Kronthaler, Laura; van der Linden, Bart; Rodewald, Katia; Rieger, Bernhard; Fischer, Roland A.; Xia, Yongde
Abstract : Photocatalytic Hydrogen Generation In article number 2200552, Mian Zahid Hussain, Yongde Xia, and co‐workers present 3D printed monolith composites derived from Ti‐metal organic framework (MOF) mixed with boehmite as promising photocatalysts, exhibiting a hydrogen evolution reaction (HER) performance 5 times higher than Ti‐MOF‐derived TiO2 /C powder. Moreover, deposition of Pt onto 3D printed monolith by an atomic layer deposition approach provides additional active sites and further enhances the photocatalytic HER activity by 30%.